matthewatalla
matthewatalla
01-09-2020
Mathematics
contestada
Simplify 3x - 4 - 5x = 6 + 4x + 2
Respuesta :
Milkias22
Milkias22
02-09-2020
Answer:
x=-2
Step-by-step explanation:
-2x-4=8+4x
-6x=8+4
-6x=12
divide both side by -6
x=-2
Answer Link
VER TODAS LAS RESPUESTAS ( 33+ )
Otras preguntas
Your friend Abbie is making a movie. She is filming a fancy dinner scene and she has two types of candles on the table. She wants to determine how long the cand
i need help badly emergency!!
Which value from the set 6, 11, 13, 25 makes ( y - 7) squared = 36
A transformer will not back-feed until it is mounted on a pole. A. True B. False
what are nutrients the Venus flytrap use and need
Identify the reagents a-i that you would use to accomplish each of the following transformations. a) CH₃CH₂OH a→ CH₃COOH b) C₆H₆ b→ C₆H₅Cl c) CH₃CH₂COOH c→ CH₃C
Using front-end estimation, what is the correct estimation of the sum, 23+33+44+51+31 -A. 180B. 170C. 160D. 150
A transformer will not back-feed until it is mounted on a pole. A. True B. False
EFFECTS OF ANTHROPOCENTRIC MODEL
If you select a marble without looking, how likely is it that you will pick a black one?